Tax compliance in the digital era: An empirical analysis of perceived justice, trust, tax morale, and knowledge among the younger generation - Mohammad, Christania Hernita Natasha; Mabrur, Azas (Educoretax, 2025)
This study aims to examine the influence of tax morale, perceptions of fairness, trust in government, and tax knowledge on the tax compliance level of Generation Z and Millennials in Palu City. A quantitative approach was employed, utilizing primary data collected through questionnaires distributed to 400 respondents. Data analysis was conducted using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results indicate that tax morale and tax knowledge have a positive and significant effect on tax compliance. These findings affirm that higher levels of tax morale and tax knowledge among taxpayers lead to greater compliance with tax obligations. Conversely, perceptions of fairness and trust in government do not significantly affect tax compliance, suggesting that these aspects are not yet strongly perceived by taxpayers as motivating factors for fulfilling tax obligations. Based on these results, the study recommends enhancing tax education for younger generations, strengthening moral values through social programs and tax volunteer initiatives, and improving government transparency and accountability in tax management to build public trust. This research provides valuable insights for developing strategies to increase tax compliance among the younger population, particularly in regional contexts.